Pengaruh Kepadatan Penduduk Ddn Keseimbangan Pangan terhadap Kesejahteraan Masyarakat di Provinsi Sumatera Utara - Ima Tri Wardani; Tri Inda Fadhila Rahma (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
This study aims to examine the effect of population density and food balance on the welfare of the people of North Sumatra Province. This study uses a type of data that is descriptive quantitative, namely using secondary data types obtained from official websites such as the Central Bureau of Statistics of North Sumatra Province and others. The analysis technique used in processing the data is using multiple linear regression analysis. The results of this study can be concluded that the population has a significant effect and has a negative relationship to community welfare. Food balance has a significant effect and has a negative relationship to people's welfare. simultaneously explained on the variables of population density and food balance which together influence the welfare of the people of North Sumatra Province.